1996
DOI: 10.1148/radiology.201.2.8888251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foot and ankle MR imaging on clinical decision making.

Abstract: MR imaging of the foot and ankle has an effect on clinical decision making. Regardless of the clinician's confidence in diagnosis, MR imaging consistently plays a central role in further defining the diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…10,25,26 It has also been stated that MR is the best noninvasive method for cartilage imaging. 27,28 In a clinical setup, however, restrictions in scan time limit SNR and spatial resolution and consequently the diagnostic performance.…”
Section: Discussionmentioning
confidence: 99%
“…10,25,26 It has also been stated that MR is the best noninvasive method for cartilage imaging. 27,28 In a clinical setup, however, restrictions in scan time limit SNR and spatial resolution and consequently the diagnostic performance.…”
Section: Discussionmentioning
confidence: 99%
“…The latter has rarely been applied to the assessment of diagnostic imaging (18) because of perceived issues associated with randomizing patients to a nonimaging policy (27,28). Whereas the within-group design of our study that used before-andafter questionnaires is similar to that used in many other studies (13)(14)(15)(16)19,29), the incorporation of a randomized comparison group has allowed us to control for changes over time that occur whether or not imaging is performed. There were, in fact, marked changes in the control group over time in all aspects of clinical diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators in some studies (19,20,29,30) who reported considerable changes in diagnoses, treatment plan, and diagnostic and therapeutic confidence after either CT or MR imaging acknowledged that patient symptoms could change in the interval between assessment and imaging. Another limitation of this type of evaluation is that clinicians may not actually follow their reported treatment plan.…”
Section: Discussionmentioning
confidence: 99%
“…This has been utilized in a variety of studies (3)(4)(5)(6)(7)(8)(9). Some developments of this simple approach attempt to take into account changes in diagnoses that might arise as a result of the test.…”
mentioning
confidence: 99%
“…Some developments of this simple approach attempt to take into account changes in diagnoses that might arise as a result of the test. These include applying the analysis only to the "retained" (or unchanged) diagnoses (3,10) and simple attempts to adjust for changes in (post-test) diagnoses (as expounded and utilized by Omary et al and others (11)(12)(13)(14).…”
mentioning
confidence: 99%